Exploring Environmental Ethics An Introduction - Smith, Kimberly K. (AESS Interdisciplinary Environmental Studies and Sciences Series,, 2018)
This book is designed as a basic text for courses that are part of an interdisciplinary program in environmental studies. The intended reader is anyone who expects environmental stewardship to be an important part of his or her life, as a citizen, a policy maker, or an environmental management professional. In addition to discussing major issues in environmental ethics, it invites readers to think about how an ethicist's perspective differs from the perspectives encountered in other environmental studies courses. Additional topics covered include corporate social responsibility, ecological citizenship, property theory, and the concept of stewardship as a vocation.